1985
DOI: 10.2135/cropsci1985.0011183x002500030015x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Effect on Nodulation of Soybean by Bradyrhizobium japonicum1

Abstract: It is not known whether NO−3 inhibition of nodulation is primarily due to effects on the host plant or on the bacterials train. This study was conducted to evaluate the effect of NO−3 on nodule appearance and development of nitrogenase (acetylene reduction) activity of various Glycine max (L.) Merr. cultivar ✕ Bradyrhizobiumja ponicum (Kirchner) Buchanan strain combinations. Plants were grown hydroponically in controlled environment cabinets. NO−3 was either resupplied daily (“maintained”) during the growth pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 0 publications
5
62
0
2
Order By: Relevance
“…It has also been reported that symbiotic efficiency of soybean plants grown on NO3-is slightly affected by B. japonicum strain (18), but it appears that the host plant is in primary control of nodulation in the presence of NO3 (3,8). Once nodulation has occurred, subsequent nodulation on new roots of normal plants is suppressed by a plant process called autoregulation (14,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that symbiotic efficiency of soybean plants grown on NO3-is slightly affected by B. japonicum strain (18), but it appears that the host plant is in primary control of nodulation in the presence of NO3 (3,8). Once nodulation has occurred, subsequent nodulation on new roots of normal plants is suppressed by a plant process called autoregulation (14,21).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate inhibition of nodulation is a common regulatory feature of legume root nodule symbiosis which is primarily controlled by the host plant (3,8). Split-root studies have demonstrated a localized NO3-effect on nodulation in soybean (1 3) and clover (2).…”
mentioning
confidence: 99%
“…Waterer and Vessey (1993) reported that inhibition of nodulation is dependent on the concentration of N in the soil solution and that a depletion of inhibitory concentrations (as might occur in the root zone due to active plant N uptake) could provide a window during which nodulation could occur. Gibson and Harper (1985) similarly reported that evidence of nodulation on plants was observed when the growing plant depleted nitrate levels. Although spring soil tests indicated relatively high levels of nitrate N at Fort Vermillion in 1996, it is likely that rhizosphere levels of nitrate-N were depleted relative to the bulk soil due to active plant uptake and thus were not inhibitory to nodulation.…”
Section: Nodulationmentioning
confidence: 93%
“…Although sensitivity of nodulation to NO3-has been the subject of numerous studies, no definitive reports have been published which elucidate the mechanisms of inhibition. For soybean it appears that the host plant, rather than the bacterial strain, is in primary control of the level of N2 fixation (5). With Since the nts mutants selected by Gresshofls group were derived from the cultivar Bragg which is a Maturity Group VII line and cannot be grown to maturity under Midwest growing conditions, the current study was initiated to select nodulation mutants from a background which can be field tested in the major Midwest soybean production area.…”
mentioning
confidence: 99%